Effects of Milling on Surface Integrity of Low-Carbon Steel - Rodrigues, Alessandro Roger [UNESP]; Matsumoto, Hidekasu [UNESP]; Yamakami, Wyser Jose [UNESP]; Tokimatsu, Ruis Camargo [UNESP]; Menezes, Miguel Angelo [UNESP]; Suyama, Daniel Iwao [UNESP]; Norcino, Adriana Bruno [UNESP]; Vendrame, Saimon [UNESP] (American Institute of Physics (AIP), 2010)
This work measured the effect of milling parameters on the surface integrity of low-carbon alloy steel. The Variance Analysis showed that only depth of cut did not influence on the workpiece roughness and the Pearson's Coefficient indicated that cutting speed was more influent than tool feed. All cutting parameters introduced tensile residual stress in workpiece surface. The chip formation mechanism depended specially on cutting speed and influenced on the roughness and residual stress of workpiece.
Keywords: Milling; Surface Integrity